Criminal Confrontation Of Intolerance And Extremism (A Comparative Study Between Islamic Jurisprudence And Positive Criminal Laws) - Hussein Fayyad, Abbas; Neama Aboud, Ismail (Opción, 2019)
Not long ago, some of our Muslim societies have been pluged by lethal diseas- es at the intellectual level, reflected negatively on the security and stability of individuals in it. The bonds have broken, hatred has increased and extremism and blind fanaticism have rebounded, and the uniqueness speech was above the speech of unity and forgiveness, which threatened the state entity and existence, and exhausted its economy and resources because of the excessive customizations to combat the consequences of all that, represented by terror- ism in all its forms and pictures, and about these Data, we saw to wading in a subject of our sense of its importance in this area which pivoting around the wondering about the position of international and national legislation on the issue of intolerance and hyperbole and its impact on peaceful coexistence, That is preceded by clarifying of the concept of fanaticism and hyperbole in accordance with Islamic law.